Influence of the pilates method in the improvement of pain in patients with chronic non-specific lowback pain: a systematic review - Almeida Lacerda, Brunna Bheatrys (2023)
background and objectives: The Pilates method consists of an exercise program that integrates the body and mind through physical conditioning, aims to expand the capacity of movements and thus increase control, muscle balance, strength and body awareness, working the body as a whole, being highly sought after by people looking to prevent or rehabilitate chronic nonspecific low back pain. This study aims to evaluate the influence of the Pilates method in patients with chronic nonspecific low back pain. Contents: A systematic review was carried out, with a search in the main databases related to the health area: PubMed, PEDro, Scielo, Embase, Biblioteca Virtual da Saúde (BVS) e Web of Science, in Portuguese and English, using descriptors that meet the research question.  Selection criteria based on strategy PICO: adults 18-65 years with non-specific chronic low back pain; intervention - Pilates method; comparison – control group; outcomes – improvement of pain. After the search, 15 articles of the clinical trial type from 2006 to 2021 Conclusion: The present systematic review concludes that the Pilates method positively influences functional disability, flexibility, kinesiophobia and general health level, being directly linked to pain improvement in patients with chronic nonspecific low back pain and, consequently, improving their quality of life at short and medium term. However, further studies  it's needed to assess the influence of the Pilates method in patients with long-term chronic nonspecific low back pain.